The role of demographic characteristics in US medical students’ professional well-being and medical school experiences: An intersectional approach - Yuchen Liu; Aleeza Amin; Patricia Frazier (PLoS ONE, 2025)
Introduction Previous findings have been mixed about the role of demographic characteristics in medical students’ well-being and school experiences when those characteristics were examined in isolation. The aim of this study was to investigate the roles of gender, race and ethnicity, and sexual orientation in medical students’ professional well-being and medical school experiences using an intersectional approach. Method We analyzed data from the 2019–2022 Association of American Medical Colleges Graduation Questionnaire ( N = 66,795). The independent variable was intersectional groups, composed of 16 intersectional groups that combined various genders, races and ethnicities, and sexual orientations. The outcome variables were professional well-being (i.e., burnout, career regret) and medical school experiences (i.e., general mistreatment, discrimination, emotional climate, faculty-student interaction, faculty professionalism, and satisfaction with medical education). Given the large sample, we focused on effect sizes versus statistical significance. Results The intersectional groups differed from each other on all professional well-being and all medical school experience variables except emotional climate, with at least small effect sizes (ηp 2 ≥ .01). Black female sexual minority students reported the most negative outcomes on all variables. The largest differences were primarily with White male heterosexual (e.g., discrimination: d = 1.68, 95% CI [1.53, 1.84]) and White female heterosexual (e.g., disengagement: d = 0.63, 95% CI [0.48, 0.79]) students. However, being a member of a greater number of marginalized groups was not necessarily associated with more negative outcomes, and patterns of group differences varied across domains of professional well-being and medical school experiences. Discussion Examining the combination of medical students’ gender, race and ethnicity, and sexual orientation yielded larger and more consistent effect sizes than examining each factor individually, suggesting that an intersectional approach can identify the unique challenges confronted by medical students from specific demographic groups.